TIME IN THERAPEUTIC RANGE (TTR) IN ATRIAL FIBRILLATION WITH WARFARIN THERAPY IN SEMARANG, INDONESIA - Della Dafina Sekarsari; Pipin Ardhianto; Erwin Kresnoadi; Mochamad Ali Sobirin (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2021)
Background: Atrial fibrillation is one of the factors forming thromboembolism. The thromboembolism can be prevented with warfarin. A side effect of warfarin is increasing the occurrence of bleeding, these therapy requires an evaluation of its usage. These evaluations can be seen in the Time in Therapeutic Range (TTR) patients. TTR is the duration in which the International Normalized Ratio (INR) patients in referral value are 2.0-3.0. TTR > 70% can prevent bleeding on FA patients with warfarin therapy.Aim: To determine TTR in patients receiving warfarin with atrial fibrillation.Methods: This study was descriptive with a cross-sectional design for six months at Dr. Kariadi Hospital Semarang. TTR was calculated using Rosendaal's Methods after collecting three INRs and patients' demographics.Results: Total subject was 111 patients with an average age of 52,63 and the TTR average is 53,75. TTR in this study was divided into two groups, that groups were poor TTR (TTR < 70%) with 82 patients (73.88%) and good TTR (≥70%) with 29 patients (26.12%).Conclusions: The average TTR in FA patients with warfarin therapy was 53,75%.